Silver-loaded zeolite adsorbent for adsorbing radioactive iodine and preparation method thereof

By corroding the Y-shaped octane zeolite and impregnating it with a silver-containing ion solution to prepare a mesoporous silver-carrying zeolite adsorbent, the problems of limited adsorption capacity and low efficiency in the prior art are solved, and radioactive iodine in the exhaust gas of spent fuel treatment plant is effectively absorbed.

CN119746808APending Publication Date: 2025-04-04CHINA INSTITUTE OF ATOMIC ENERGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510012316.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the adsorbent used in radioactive iodine in the exhaust gas of spent fuel aftertreatment plants has limited adsorption capacity and low adsorption efficiency, making it difficult to meet the requirements of efficient treatment.

Method used

A mesoporous silver-carrying zeolite adsorbent is provided, which expands the pore size by corroding the Y-shaped octane zeolite, and immerses it with a silver-containing ion solution to prepare a silver-carrying zeolite adsorbent to improve its adsorption effect on radioactive iodine.

Benefits of technology

It improves the adsorption capacity and efficiency of silver-loaded zeolite adsorbent, can effectively adsorb gaseous organic iodine, and is suitable for the purification of exhaust gas in spent fuel after-treatment plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746808A_ABST
    Figure CN119746808A_ABST
Patent Text Reader

Abstract

The invention provides a silver-loaded zeolite adsorbent for adsorbing radioactive iodine as well as a preparation method and application of the silver-loaded zeolite adsorbent. The silver-loaded zeolite adsorbent provided by the invention comprises mesoporous faujasite and a silver element, the aperture of the mesoporous faujasite is 0.38-67.39 nm, and the mesopore proportion is 36.54%-53.87%. The silver-loaded zeolite adsorbent disclosed by the invention is rich in mesopores, large in specific surface area and high in silver loading amount, and has an excellent adsorption effect on radioactive iodine and iodide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of radioactive element adsorption, and in particular to a silver-loaded zeolite adsorbent for adsorbing radioactive iodine and a preparation method thereof. Background Art

[0002] With the continuous growth of global energy demand, the increasing depletion of fossil energy and the restriction of greenhouse gas emissions, nuclear energy has attracted more and more attention as an efficient, safe, low-carbon and economical alternative energy source. The use of nuclear energy will be accompanied by the release of a large number of volatile radioactive nuclides. Among them, I 129 and I 131 Due to its high volatility and mobility, it not only causes harm to the environment, but is also easily absorbed and reacted by the body, thus affecting its metabolic process. Therefore, the effective capture of radioactive iodine is crucial for public health and environmental protection. In addition, radioactive iodine that enters the reprocessing solution during the nuclear fuel reprocessing process will also reduce the quality of uranium and plutonium products and increase the amount of contaminated solvents. Therefore, the removal and safe disposal of radioactive iodine is of great significance in the safe, environmentally friendly and economical use of nuclear energy.

[0003] At present, the purification of radioactive iodine in my country's spent fuel reprocessing process is too simple, and the relevant technology and process research is relatively weak. Therefore, a more efficient purification method is needed for the radioactive iodine in the tail gas of the spent fuel reprocessing plant.

[0004] There are many widely used methods for removing radioactive iodine from spent fuel, such as wet capture and solid capture. Wet capture uses liquid as an absorbent to make gaseous iodine contact with the absorption liquid to react and achieve iodine absorption. Solid capture uses solid adsorbents to adsorb and enrich radioactive iodine to achieve the purpose of purification. Solid capture mainly uses silver-loaded zeolite, silver-coated alumina and silver-coated silica gel as adsorbents for adsorption. However, the adsorbents commonly used in the prior art have limited adsorption capacity and low adsorption efficiency, which makes it difficult to meet the requirements for efficient treatment of radioactive iodine in the tail gas of spent fuel reprocessing plants.

[0005] Therefore, for the treatment of radioactive iodine in the tail gas of spent fuel reprocessing plants, a high-capacity, high-efficiency and low-cost radioactive iodine adsorbent is needed that can simultaneously adsorb elemental iodine and organic iodine. Summary of the invention

[0006] In view of this, the main purpose of the present invention is to provide a mesoporous silver-loaded zeolite adsorbent for efficiently adsorbing gaseous organic iodine and its preparation method and application. The mesoporous silver-loaded zeolite adsorbent has abundant mesopores, large specific surface area, high silver loading, and has excellent adsorption effect on radioactive iodine and iodide.

[0007] To this end, the present invention provides a silver-loaded zeolite adsorbent for adsorbing radioactive iodine. The silver-loaded zeolite adsorbent comprises mesoporous faujasite and silver element. The pore size of the mesoporous faujasite is 0.38-67.39 nm, and the mesopore ratio is 36.54%-53.87%.

[0008] In some embodiments, the specific surface area of ​​the silver-loaded zeolite adsorbent is 273 m 2 / g~324m 2 / g.

[0009] In some embodiments, the weight content of silver is 25 wt % to 40 wt % relative to the total weight of the silver-loaded zeolite adsorbent.

[0010] In some embodiments, the structural formula of the mesoporous faujasite is (Na2O) a (SiO2) b (Al2O3) c (H2O) d , where a:b:c:d=9.6:14.4:1.0:23.2.

[0011] The present invention also provides a method for preparing the silver-loaded zeolite adsorbent, comprising the following steps:

[0012] Obtaining Y-type faujasite;

[0013] The Y-type faujasite is corroded by a corrosive agent to obtain a mesoporous faujasite, wherein the corrosive agent comprises a solution of NH4F;

[0014] The mesoporous faujasite zeolite is impregnated with a silver ion-containing solution to obtain the silver-loaded zeolite adsorbent.

[0015] In some embodiments, the fluoride ion concentration in the etchant is 1.25M to 9.5M.

[0016] In some embodiments, the ratio of the mass of the Y-type faujasite to the volume of the corrosive agent is 1 g:12 ml to 1 g:15 ml.

[0017] In some embodiments, the corrosion treatment time is 5 to 30 minutes.

[0018] In some embodiments, the silver ion concentration in the silver ion-containing solution is 0.1 to 1.0 mol / L.

[0019] In some embodiments, the ratio of the mass of the mesoporous faujasite to the volume of the silver ion-containing solution is 1 g:15 ml to 1 g:50 ml.

[0020] The present invention also provides the use of the silver-loaded zeolite adsorbent in adsorbing radioactive iodine or iodide, wherein the adsorption comprises contacting a gas containing radioactive iodine or iodide with the silver-loaded zeolite adsorbent.

[0021] In some embodiments, the adsorption comprises: passing a gas containing radioactive iodine or iodide through the silver-loaded zeolite adsorbent at a temperature of 100-140° C. and a gas flow rate of 200-400 ml / min.

[0022] In some embodiments, the radioiodide comprises a radioactive organic iodine.

[0023] The silver-loaded zeolite adsorbent for adsorbing radioactive iodine provided by the present invention has a larger pore size and a higher mesopore ratio, so that the internal pores and active sites are effectively utilized, and more space is provided to load silver, which is conducive to increasing the silver loading amount and providing more adsorption active sites, thereby improving the adsorption capacity of the silver-loaded zeolite adsorbent for radioactive iodine or iodide. Further, the silver-loaded zeolite adsorbent of the present invention has a higher specific surface area, which is conducive to increasing the contact area with radioactive iodine during the adsorption process, thereby having an improved adsorption efficiency. The silver-loaded zeolite adsorbent of the present invention has potential application prospects in the fields of adsorption and catalysis. The preparation method of the present invention uses ammonium fluoride to etch and expand the pores of Y-type faujasite zeolite, and then immerses the expanded zeolite in a silver-containing solution to obtain a silver-loaded zeolite adsorbent. The preparation method is simple, and the obtained silver-loaded zeolite adsorbent has a high adsorption capacity and high adsorption efficiency for radioactive iodine or iodide. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a transmission electron microscope (TEM) image of the silver-loaded zeolite adsorbent of Example 1 of the present invention.

[0025] Figure 2 This is an atomic resolution transmission electron microscope (STEMHAADF) image of the silver-loaded zeolite adsorbent of Example 1 of the present invention.

[0026] Figure 3 This is a pore size distribution diagram of the silver-loaded zeolite adsorbent of Example 1 of the present invention.

[0027] Figure 4 The pore volume distribution diagram of the silver-loaded zeolite adsorbent of Examples 1-4 of the present invention and Comparative Example 1.

[0028] Figure 5 Field emission scanning electron microscope energy spectrum of the silver-loaded zeolite adsorbent of Examples 1 and 3-4 of the present invention.

[0029] Figure 6 It is an adsorption curve diagram of methyl iodide adsorbed by the silver-loaded zeolite adsorbent of Examples 1-4 of the present invention and Comparative Example 1.

[0030] Figure 7 This is an adsorption curve diagram of methyl iodide adsorbed by the silver-loaded zeolite adsorbent of Example 1 of the present invention at different temperatures. DETAILED DESCRIPTION

[0031] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0033] It should be noted that, in the embodiments of the present invention, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a method or device including a series of elements includes not only the elements explicitly stated, but also other elements not explicitly listed, or also includes elements inherent to the implementation of the method or device. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the existence of other related elements in the method or device including the element.

[0034] It should be noted that the terms "first\second\third" involved in the embodiments of the present invention are only used to distinguish similar objects, and do not represent a specific order for the objects. It is understandable that the specific order or sequence of "first\second\third" can be interchanged where permitted. It should be understood that the objects distinguished by "first\second\third" can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein.

[0035] Zeolite molecular sieves have attracted much attention and have been widely used in the fields of catalysis and adsorption due to their uniform pores and high stability. However, the pore diameter inside zeolite molecular sieves limits the entry of adsorbed molecules, so that the internal pores and active sites cannot be effectively utilized.

[0036] In view of this, the present invention provides a silver-loaded zeolite adsorbent for adsorbing radioactive iodine, the silver-loaded zeolite adsorbent comprising mesoporous faujasite and silver element, the pore size of the mesoporous faujasite is 0.38-67.39 nm, and the mesopore ratio is 36.54%-53.87%. The present invention is conducive to expanding the internal pore diameter of the zeolite by making the pore size of the mesoporous faujasite within the above range, so that the adsorbed radioactive iodine or iodide molecules can enter therein, improving the utilization rate of the internal pores and active sites, and improving the adsorption capacity of the silver-loaded zeolite adsorbent. Exemplarily, the pore size of the mesoporous faujasite can be 0.38 nm, 0.50 nm, 0.65 nm, 0.80 nm, 1.0 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 50 nm, 60 nm, 65 nm, 67.39 nm or a value between the ranges formed by any two of them. By making the mesopore ratio of the mesoporous faujasite zeolite within the above range, it is beneficial to provide more silver-loading sites, increase the silver loading of the silver-loaded zeolite adsorbent, and then provide more adsorption active sites, further improving the adsorption capacity of the silver-loaded zeolite adsorbent. In addition, faujasite zeolite has good structural stability, which is beneficial to improve the service life of the silver-loaded zeolite adsorbent. Exemplarily, the mesopore ratio of the mesoporous faujasite zeolite can be 36.54%, 37.5%, 40%, 45%, 50%, 53.87% or a value between the ranges consisting of any two of them.

[0037] In some embodiments, the specific surface area of ​​the silver-loaded zeolite adsorbent is 273 m 2 / g~324m 2 / g. By making the specific surface area of ​​the silver-loaded zeolite adsorbent within the above range, on the one hand, it is beneficial to increase the silver-loading sites, increase the silver-loading amount of faujasite zeolite, and thus increase the adsorption capacity of the silver-loaded zeolite adsorbent; on the other hand, it is beneficial to increase the contact area between the adsorbed radioactive iodine or iodide molecules and the adsorption active sites, thereby improving the adsorption kinetics and the adsorption efficiency. For example, the specific surface area of ​​the silver-loaded zeolite adsorbent can be 273m 2 / g, 285m 2 / g, 290m 2 / g、300m 2 / g, 315m 2 / g, 324m 2 / g or a value between the ranges consisting of any two of them.

[0038] In some embodiments, the weight content of silver is 25wt% to 40wt% relative to the total weight of the silver-loaded zeolite adsorbent. By making the silver content in the silver-loaded zeolite adsorbent within the above range, more adsorption active sites can be provided, thereby improving the adsorption capacity and adsorption efficiency of the silver-loaded zeolite adsorbent. Exemplarily, relative to the total weight of the silver-loaded zeolite adsorbent, the weight content of silver can be 25wt%, 27wt%, 30wt%, 31wt%, 33wt%, 35wt%, 37wt%, 40wt% or a value between the ranges consisting of any two of them. In some preferred embodiments, relative to the total weight of the silver-loaded zeolite adsorbent, the weight content of silver is 25wt% to 30wt%.

[0039] In some embodiments, the structural formula of the mesoporous faujasite is (Na2O) a (SiO2) b (Al2O3) c (H2O) d , wherein a:b:c:d=9.6:14.4:1.0:23.2. In the faujasite zeolite having the above composition, the mesopores between the zeolite grains are evenly distributed, thereby providing more silver-carrying active sites and improving the adsorption capacity of the silver-carrying zeolite. In addition, the above faujasite zeolite has a pore with a twelve-oxygen ring structure and has a strong structural stability, which is conducive to improving the service life of the silver-carrying zeolite adsorbent.

[0040] The second aspect of the present invention provides a method for preparing the silver-loaded zeolite adsorbent according to the first aspect of the present invention, comprising the following steps: obtaining Y-type faujasite;

[0041] The Y-type faujasite is corroded by a corrosive agent to obtain a mesoporous faujasite, wherein the corrosive agent comprises a solution of NH4F;

[0042] The mesoporous faujasite zeolite is impregnated with a silver ion-containing solution to obtain the silver-loaded zeolite adsorbent.

[0043] The method of the present invention uses a corrosive agent to corrode the Y-type faujasite zeolite, thereby expanding the internal pore diameter of the zeolite, increasing the pore size and the mesopore ratio, thereby facilitating the improvement of the active sites and adsorption area of ​​the silver-loaded zeolite adsorbent, and improving the adsorption capacity and adsorption kinetics of the silver-loaded zeolite adsorbent. The silver-loaded zeolite is obtained by treating with an ammonium fluoride (NH4F) solution and then dissolving and impregnating with silver ions. The method of the present invention is simple to operate, low in cost, and has a good prospect for application in the nuclear industry.

[0044] In the present invention, the Y-type faujasite zeolite can be prepared by a method known to those skilled in the art, or can be commercially available. For example, the Y-type faujasite zeolite can be prepared by mixing aluminum-rich silica gel (Na2O:Al2O3:10SiO2:140H2O) and silica-rich gel (5.3Na2O:1.8K2O:Al2O3:2.2SiO2:122H2O) after aging. Exemplarily, Y-type faujasite zeolite can also be prepared by the following method: dissolve 1.0 g NaOH in 16.0 g H2O, then add 5.0 g colloidal Si2O under vigorous stirring to obtain Sol-A, dissolve 1.14 g NaOH in 6.0 g H2O, add 0.52 g Al(OH)3) to obtain Sol-B, mix Sol-A and Sol-B in a ratio of 1Al2O3:10SiO2:8.0Na2O:0.36DOAC:420H2O, mix in an ice bath and then mature to obtain the obtained product.

[0045] In some embodiments, the Y-type faujasite zeolite is prepared by the following method:

[0046] S1-1, 0.66 mol / L sodium hydroxide (NaOH) solution and aluminum isopropoxide (C9H 21 AlO3) according to m(NaOH):m(C9H 21 AlO3)=9.49∶3.75 ratio and stir for 2h.

[0047] S1-2, using SiO2 30% aqueous solution as silicon source, slowly adding it into the mixed solution of aluminum isopropoxide and sodium hydroxide, sealing, and preliminarily ripening in a water bath at 25°C for 24 hours to obtain a colloid.

[0048] S1-3, the colloid is transferred to a polypropylene bottle and sealed, and is secondarily aged in an oven at 38°C for 24 hours, and then the colloid is treated at 60°C for 48 hours, and then centrifuged at a low speed to obtain a solid. The solid obtained by centrifugation is washed to a pH value of 8 to 9, and dried at room temperature to obtain a Y-type faujasite zeolite (FAU) sample.

[0049] The structural formula of Y-type faujasite prepared by the above method is (Na2O) a (SiO2) b (Al2O3) c (H2O) d , wherein a:b:c:d=9.6:14.4:1.0:23.2. The Y-type faujasite zeolite has a pore with a twelve-membered ring structure, has high strength, and the mesopores between the zeolite grains are evenly distributed, providing a good structural basis for subsequent silver loading. The silver-loaded zeolite adsorbent based on the Y-type faujasite zeolite has good structural stability, which is beneficial to improving the service life of the silver-loaded zeolite adsorbent.

[0050] In some embodiments, the fluoride ion concentration in the etchant is 1.25mol / L to 9.5mol / L. By making the fluoride ion concentration in the etchant within the above range, it is beneficial to obtain a larger proportion of mesopores. Exemplarily, in the etchant, the fluoride ion concentration can be 1.25mol / L, 1.5mol / L, 2.5mol / L, 3.5mol / L, 4.5mol / L, 4.55mol / L, 4.60mol / L, 4.65mol / L, 4.7mol / L, 5.5mol / L, 6.5mol / L, 7.5mol / L, 8.5mol / L, 9.5mol / L or a value between the ranges consisting of any two of them. In some preferred embodiments, the fluoride ion concentration in the etchant is 4.5mol / L to 4.7mol / L.

[0051] In some embodiments, the ratio of the mass of the Y-type faujasite zeolite to the volume of the etchant is 1g:12ml to 1g:15ml. By making the ratio of the mass of the Y-type faujasite zeolite to the volume of the etchant within the above range, it is beneficial for the etchant to fully contact and react with the Y-type faujasite zeolite, expand the internal pore diameter of the Y-type faujasite zeolite, and increase the pore size and mesopore ratio of the Y-type faujasite zeolite, thereby making full use of the active sites inside the faujasite zeolite and improving the adsorption capacity of the subsequently prepared silver-loaded zeolite adsorbent.

[0052] In some embodiments, the corrosion treatment time is 5 to 30 minutes. The corrosion treatment time has a strong correlation with the size of the mesopores. By making the corrosion treatment time within the above range, it is beneficial to obtain a silver-loaded zeolite adsorbent with a preferred mesopore ratio. Exemplarily, the corrosion treatment time can be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes or a value between the ranges consisting of any two of them.

[0053] In some embodiments, the silver ion concentration in the silver ion solution is 0.1 to 1.0 mol / L. By making the silver ion concentration in the silver ion solution within the above range, it is beneficial for the silver-loaded zeolite adsorbent to have a suitable silver loading amount to improve the adsorption effect of the silver-loaded zeolite adsorbent. Exemplarily, the above silver ion concentration can be 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L or a value between the ranges consisting of any two of them.

[0054] In some embodiments, the ratio of the mass of the mesoporous faujasite to the volume of the silver ion-containing solution is 1g:15ml to 1g:50ml. By making the ratio of the mass of the mesoporous faujasite to the volume of the silver ion-containing solution within the above range, it is beneficial for the silver ions to fully infiltrate the Y-type faujasite, thereby fully replacing the ions inside the faujasite, so that the silver ions are loaded onto the faujasite to provide active adsorption sites. Exemplarily, the ratio of the mass of the mesoporous faujasite to the volume of the silver ion-containing solution can be 1g:15ml, 1g:20ml, 1g:25ml, 1g:30ml, 1g:35ml, 1g:40ml, 1g:45ml, 1g:50ml or a value between the ranges consisting of any two of them.

[0055] The third aspect of the present invention also provides the use of the silver-loaded zeolite adsorbent described in the first aspect in adsorbing radioactive iodine or iodide, wherein the adsorption comprises contacting the gas containing radioactive iodine or iodide with the silver-loaded zeolite adsorbent. The silver-loaded zeolite adsorbent of the present invention can achieve high-efficiency adsorption by contacting with the gas containing radioactive iodine or iodide, is simple to operate, and has good application prospects in the field of nuclear industry.

[0056] In some embodiments, the adsorption comprises passing the radioactive iodine or iodide-containing gas through the silver-loaded zeolite adsorbent at 100-140° C. at a gas flow rate of 200-400 ml / min. Adsorption of the radioactive iodine or iodide-containing gas by the silver-loaded zeolite adsorbent under the above conditions is conducive to improving the adsorption capacity and efficiency. Under the above adsorption conditions, the adsorbent prepared according to the method of the present invention, for example, with a silver loading of 30 wt%, can process 712.72 g CH3 per kg of adsorbent. 131 I, thereby achieving the purpose of removing radioactive iodine or iodide.

[0057] In the present invention, the gas containing radioactive iodine or iodide may be from a source known to those skilled in the art, such as waste gas from a spent fuel reprocessing process.

[0058] In some embodiments, the radioiodide comprises a radioactive organic iodine.

[0059] The following describes the embodiments of the present invention in detail through specific examples. It should be understood that these examples are only exemplary and cannot be used as a limitation on the scope of the present invention.

[0060] Example

[0061] Example 1

[0062] 9.49 g of NaOH was prepared into a solution with a concentration of 0.66 mol / L and mixed with 3.75 g of aluminum isopropoxide (C9H21 AlO3) and stirred for 2 hours. Take 35.25g SiO2 30% aqueous solution as the silicon source, slowly add it to the above-mentioned aluminum isopropoxide and sodium hydroxide mixture, seal it and place it in a water bath at 25°C, and preliminarily mature it for 24 hours to obtain a colloid. Then transfer the above colloid to a polypropylene bottle, seal it, and mature it in an oven at 38°C for 24 hours. Treat the matured colloid at 60°C for 48 hours. Centrifuge at low speed to obtain a solid, wash it until the pH is in the range of 8 to 9, and dry it at room temperature for 48 hours to obtain a faujasite zeolite (FAU) sample.

[0063] The faujasite sample was mixed with 4.5 mol / L NH4F solution for etching, wherein the ratio of the mass of the faujasite sample to the volume of the ammonium fluoride solution was 1 g:12 ml. The etching was carried out at 25°C for 30 min under stirring at 500 rpm. After the reaction was completed, the solid product was repeatedly washed with 80°C distilled water within 5 minutes until the F ion concentration in the solid product was less than 1 ppm, and then dried at 110°C for 10 hours to obtain the expanded faujasite. The reproducibility of this treatment depends largely on the separation speed of the zeolite crystals from the etching solution and the degree of cleaning.

[0064] The expanded faujasite zeolite was mixed with 1.0 mol / L AgNO3 solution at a solid-liquid ratio of 1 g:50 ml. After ultrasonic dispersion for 15 min, the mixture was stirred and immersed for 4 h in the dark, centrifuged, and dried at 110°C for 24 h to obtain a silver-loaded zeolite adsorbent.

[0065] Embodiment 2-4

[0066] A silver-loaded zeolite adsorbent was prepared by a method similar to that of Example 1, except that the concentration of NH4F used was adjusted according to the data shown in Table 1.

[0067] Comparative Example 1

[0068] 9.49 g of NaOH solution was mixed with 3.75 g of aluminum isopropoxide (C9H 21 AlO3) and stirred for 2 hours. Take 35.25g SiO2 30% aqueous solution as the silicon source, slowly add it to the above-mentioned aluminum isopropoxide and sodium hydroxide mixture, seal it and place it in a water bath at 25°C, and preliminarily mature it for 24 hours to obtain a colloid. Then transfer the above colloid to a polypropylene bottle, seal it, and mature it in an oven at 38°C for 24 hours. Treat the matured colloid at 60°C for 48 hours. Centrifuge at low speed to obtain a solid, wash it until the pH is in the range of 8 to 9, and dry it at room temperature for 48 hours to obtain a faujasite zeolite (FAU) sample.

[0069] Faujasite was mixed with 1.0 mol / L AgNO3 solution at a solid-liquid ratio of 1 g:50 ml, and the mixture was ultrasonically dispersed for 15 min, stirred and immersed for 4 h in a dark environment, centrifuged, and dried at 110°C for 24 h to obtain a silver-loaded zeolite adsorbent.

[0070] The silver-loaded zeolite adsorbent obtained above was analyzed according to the following method:

[0071] (1) TEM and STEM HAADF testing

[0072] The samples were analyzed by field emission transmission electron microscopy (TEM), using a FEI Talos F200x instrument equipped with a Super-X EDS energy spectrometer.

[0073] The TEM image of the sample prepared in Example 1 is shown in Figure 1 , STEM HAADF diagram is shown in Figure 2 .in, Figure 1 It shows that the silver oxide is evenly distributed. Figure 2 The average particle size of the silver oxide particles was shown to be 8.33 nm.

[0074] (2) Pore size analysis

[0075] The pore size of the sample was analyzed by using a specific surface area and pore size analyzer. The sample was purged in a 120°C airflow for 12 hours before the test. Test conditions: 77K N2. Instrument manufacturer: Micromeritics Instruments, USA, instrument model: Micromeritics ASAP2460, USA. The pore size distribution diagram was obtained through adsorption and desorption test, and then the pore size ratio was obtained.

[0076] The sample prepared in Example 1 was subjected to pore size analysis according to the above method, and the pore size distribution diagram is shown in Figure 3 .

[0077] The samples prepared in Examples 1, 3-4 and Comparative Example 1 were subjected to pore size analysis according to the above method, and the pore volume distribution diagram is shown in Figure 4 .Depend on Figure 4 It can be seen that the silver-loaded zeolites prepared in Examples 1 and 3-4 have a larger pore volume than the silver-loaded zeolite prepared in Comparative Example 1.

[0078] (3) Field emission scanning electron microscope energy spectrum

[0079] Field emission scanning electron microscope (SEM-EDS) was used for EDS analysis to qualitatively and quantitatively analyze the element composition and content in the sample. The test instrument was an APREO microscope from FEI Company of the United States, with a voltage of 2KV and a current of 25A.

[0080] The samples of Examples 1, 3-4 were tested according to the above method, and the test results are shown in Figure 5 , wherein (a) is the silver-loaded zeolite of Example 1; (b) is the silver-loaded zeolite of Example 3; and (c) is the silver-loaded zeolite of Example 4.

[0081] (4) Nitrogen adsorption and desorption test:

[0082] The adsorbent type is determined by the adsorption-desorption isotherm, the pore size ratio is obtained by the pore size distribution diagram, and the specific surface area data is obtained by the BET data. Before the test, the sample was purged in a 120℃ airflow for 12 hours. Test conditions: 77KN2.

[0083] (5) Silver loading test:

[0084] Analyze the change in the content of Ag in the impregnation solution before and after loading to estimate the silver loading of the zeolite material. The Ag ion analysis method uses standard sodium hydroxide solution as the titrant and potassium chromate as the indicator to titrate the concentration of the AgNO3 solution before and after impregnation, and calculate ΔCAgNO3. ΔCAgNO3 = AgNO3 solution concentration before impregnation - AgNO3 solution concentration after impregnation. The silver loading is calculated using the following formula.

[0085]

[0086] (6) Adsorption performance test:

[0087] The methyl iodide to be dynamically adsorbed is placed in a 100mL constant temperature iodine storage tank set to the research temperature. The evaporated CH3I gas is mixed in the mixer with nitrogen as the carrier gas and passed into the fixed bed pre-loaded with silver-loaded zeolite adsorbent sample and quartz sand. The fixed bed temperature can be controlled by a heater. The tail gas after adsorption enters the NaOH solution for absorption. The gas phase methyl iodide concentration at the inlet and outlet of the fixed bed is sampled through a three-way pipe on the pipeline entering and exiting the fixed bed and entering the gas chromatography analysis. The adsorption experimental conditions are as follows: temperature is 100℃, flow rate is 300mL / min, pressure is 0.07Pa,.

[0088] The adsorption amount can be calculated as follows:

[0089]

[0090] Q t is the adsorption amount of the material at time t, mg / g; F is the gas volume flow rate, mL / min; t is the adsorption time, min; C0 is the initial mass concentration of iodine, mg / m 3 ; C i is the mass concentration of iodine in the tail gas after adsorption for a certain period of time, mg / m 3 ; W is the loading amount of adsorbent, g.

[0091] At 100°C, the gas containing radioactive methyl iodide was continuously passed through a column filled with mesoporous silver-loaded faujasite zeolite adsorbent at a flow rate of 300 ml / min. 131 I concentration is 2.31*10 12 Bq / L. Measurement of CH3 in the gas after adsorption of radioactive methyl iodide 131 The concentration of I was calculated, and the amount of methyl iodide that could be adsorbed per gram of the adsorbent was calculated. The silver-loaded zeolite adsorbents prepared in the above Examples 1-4 and Comparative Example 1 were subjected to nitrogen adsorption and desorption tests and silver loading tests, and the results are recorded in Table 1.

[0092] Table 1

[0093]

[0094] It can be seen from the results in Table 1 that, compared with Comparative Example 1, the silver-loaded zeolite adsorbents prepared in Examples 1-4 of the present invention have a higher mesopore ratio, and the adsorption amount of organic iodine per unit volume of the sample is significantly improved.

[0095] The adsorption amounts of the samples of Examples 1, 3-4 and Comparative Example 1 at different time points in the adsorption performance test were plotted into adsorption amount-time curves, as shown in Figure 6 .from Figure 6 It can be seen that the silver-loaded adsorption zeolites of Examples 1, 3-4 of the present invention have significantly improved adsorption performance.

[0096] The samples of Example 1 were tested for adsorption performance at different adsorption temperatures. The results are shown in Figure 7 .Depend on Figure 7 It can be seen that the silver-loaded zeolite adsorbent of the present invention has excellent adsorption performance, and the adsorption performance is further improved as the adsorption temperature increases.

[0097] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A silver-loaded zeolite adsorbent for adsorbing radioactive iodine, characterized in that: The silver-loaded zeolite adsorbent comprises mesoporous faujasite and silver element. The pore size of the mesoporous faujasite is 0.38-67.39 nm, and the mesopore ratio is 36.54%-53.87%.

2. The silver-loaded zeolite adsorbent according to claim 1, wherein The specific surface area of ​​the silver-loaded zeolite adsorbent is 273 m 2 / g~324m 2 / g.

3. The silver-loaded zeolite adsorbent according to claim 1, wherein Relative to the total weight of the silver-loaded zeolite adsorbent, the weight content of the silver element is 25wt% to 40wt%.

4. The silver-loaded zeolite adsorbent according to claim 1, wherein The structural formula of the faujasite before silver loading is (Na2O) a (SiO2) b (Al2O3) c (H2O) d , where a:b:c:d=9.6:14.4:1.0:23.

2.

5. A method for preparing a silver-loaded zeolite adsorbent according to any one of claims 1 to 4, comprising the following steps: Obtaining Y-type faujasite; The Y-type faujasite is corroded by a corrosive agent to obtain a mesoporous faujasite, wherein the corrosive agent comprises a solution of NH4F; The mesoporous faujasite zeolite is impregnated with a silver ion-containing solution to obtain the silver-loaded zeolite adsorbent.

6. The preparation method according to claim 5, wherein: In the etchant, the fluoride ion concentration is 1.25M to 9.5M; Preferably, the ratio of the mass of the Y-type faujasite to the volume of the corrosive agent is 1g:12ml to 1g:15ml; Preferably, the corrosion treatment time is 5 to 30 minutes.

7. The preparation method according to claim 5, wherein: In the silver ion-containing solution, the silver ion concentration is 0.1 to 1.0 mol / L; Preferably, the ratio of the mass of the mesoporous faujasite to the volume of the silver ion-containing solution is 1 g:15 ml to 1 g:50 ml.

8. Use of the silver-loaded zeolite adsorbent according to any one of claims 1 to 4 in adsorbing radioactive iodine or iodide, wherein: The adsorption comprises contacting a gas containing radioactive iodine or iodide with the silver-loaded zeolite adsorbent.

9. The use according to claim 8, wherein: The adsorption comprises: passing the gas containing radioactive iodine or iodide through the silver-loaded zeolite adsorbent at a temperature of 100-140° C. and a gas flow rate of 200-400 ml / min.

10. The use according to claim 8 or 9, wherein: The radioactive iodide includes radioactive organic iodine.

Citation Information

Patent Citations

  • Process for the removal of iodine and organic iodine compounds from gases and vapors using silver-containing zeolite of the faujasite type

    US4913850A